Cost-Effectiveness of a National Sugar-Sweetened Beverage Tax to Reduce Cancer Burdens and Disparities in the United States. Issue 6 (25th August 2020) - Du, Mengxi; Griecci, Christina F; Kim, David D; Cudhea, Frederick; Ruan, Mengyuan; Eom, Heesun; Wong, John B; Wilde, Parke E; Michaud, Dominique S; Lee, Yujin; Micha, Renata; Mozaffarian, Dariush; et al.
Abstract: Background: Sugar-sweetened beverage (SSB) consumption contributes to obesity, a risk factor for 13 cancers. Although SSB taxes can reduce intake, the health and economic impact on reducing cancer burdens in the United States are unknown, especially among low-income Americans with higher SSB intake and obesity-related cancer burdens. Methods: We used the Diet and Cancer Outcome Model, a probabilistic cohort state-transition model, to project health gains and economic benefits of a penny-per-ounce national SSB tax on reducing obesity-associated cancers among US adults aged 20 years and older by income. Results: A national SSB tax was estimated to prevent 22 075 (95% uncertainty interval [UI] = 16 040-28 577) new cancer cases and 13 524 (95% UI = 9841-17 681) cancer deaths among US adults over a lifetime. The policy was estimated to cost 1.70 (95% UI = 1.50-1.95) billion for government implementation and 1.70 (95% UI = 1.48-1.96) billion for industry compliance, while saving 2.28 (95% UI = 1.67-2.98) billion cancer-related healthcare costs. The SSB tax was highly cost-effective from both a government affordability perspective (incremental cost-effectiveness ratio [ICER] = 1486, 95% UI = -3516-9265 per quality-adjusted life year [QALY]) and a societal perspective (ICER = 13 220, 95% UI = 3453-28 120 per QALY). Approximately 4800 more cancer cases and 3100 more cancer deaths would be prevented, and 0.34 billion more healthcare cost savings would be generated among low-income (federal poverty-to-income ratio [FPIR] ≤ 1.85) than higher-income individuals (FPIR > 1.85). Conclusions: A penny-per-ounce national SSB tax is cost-effective for cancer prevention in the United States, with the largest health gains and economic benefits among low-income Americans.